2015
DOI: 10.7317/pk.2015.39.2.225
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, Thermal Stability and Conductivity of New Schiff Base Polymer Containing Sulfur and Oxygen Bridges

Abstract: In this study, we proposed to synthesize thermally stable, soluble and conjugated Schiff base polymer (SbP). For this reason, a specific molecule namely 4,4'-thiodiphenol which has sulfur and oxygen bridge in its structure was used to synthesize bi-functional monomers. Bi-functional amino and carbonyl monomers namely 4,4'-[thio-bis(4,1-phenyleneoxy)]dianiline (DIA) and 4,4'-[thiobis(4,1-phenyleneoxy)]dibenzaldehyde (DIB) were prepared from the elimination reaction of 4,4'-thiodiphenol with 4-iodonitrobenzene a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 33 publications
(29 reference statements)
1
4
0
Order By: Relevance
“…After the analysis using the two-probe technique, the conductivity value of SBP was calculated as 2.35 x 10 -10 S/cm. Since it was stated in the studies that the conductivity values of undoped poly(azomethine) compounds were generally observed in the range of 1 x 10 -9 -1 x 10 -11 S/cm, the result was found to be compatible with previous studies [22]. Therefore, it turned out that the conductivity of the obtained SBP was low.…”
Section: Conductivity Of Sbpsupporting
confidence: 84%
See 2 more Smart Citations
“…After the analysis using the two-probe technique, the conductivity value of SBP was calculated as 2.35 x 10 -10 S/cm. Since it was stated in the studies that the conductivity values of undoped poly(azomethine) compounds were generally observed in the range of 1 x 10 -9 -1 x 10 -11 S/cm, the result was found to be compatible with previous studies [22]. Therefore, it turned out that the conductivity of the obtained SBP was low.…”
Section: Conductivity Of Sbpsupporting
confidence: 84%
“…DBA, a dibenzaldehyde compound obtained from the bromine elimination reaction from 4,4'-thiodiphenol and bromo-benzaldehyde, was examined by FTIR spectroscopy. In a study by Culhaoğlu and [22], the FT-IR spectra of this synthesized substance were compared and it was observed that the spectra were compatible with each other. FT-IR spectra of synthesized DBA and SBP are shown in Figure 2…”
Section: Structural Analysismentioning
confidence: 86%
See 1 more Smart Citation
“…[2][3][4][5] As a powerful technique for studying the pyrolysis mechanism of physicochemical processes, thermal analysis mainly includes differential scanning analysis (DTA), thermomechanical analysis (TMA), differential thermal gravity (TG/DTG) and differential scanning calorimetry (DSC). [6][7][8][9] The last two kinds are the most widely used approach for studying pyrolytic reaction of thermosetting resin. [10][11][12][13] In most thermal decomposition kinetic research methods, Kissinger's 14 maximum weight-loss rate method and Ozawa's 15 equivalent weight-loss percentage method are applied for dynamic computation via relation between peak temperature and heating rate of DTG and DSC curves, involving no selection of mechanism func-폴리머, 제40권 제5호, 2016년 tion and applying to any reaction order with more reliable result.…”
Section: Introductionmentioning
confidence: 99%
“…S3-S5), similar assignments have been reported in the literature for dicarbonyl monomers. 36,37 The polymers PmHOBND and PoHONPD showed weak band at 1694 and 1683 cm -1 respectively for υ C=O contributed from end on group, this band was present as a strong band in their corresponding monomers which showed that carbonyl group was converted into imine group. All the three polymers (PmHOBND, PoHONPD and PoHOAND) showed strong to medium intensity band within 1594-1620 cm -1 for υ C=N and the band within 1592-1518 cm -1 due to aromatic rings of the polymers.…”
Section: Ft-ir Spectroscopy Of Monomers and Polymersmentioning
confidence: 96%